2001
DOI: 10.1046/j.1365-2958.2001.02529.x
|View full text |Cite
|
Sign up to set email alerts
|

MlrA, a novel regulator of curli (AgF) and extracellular matrix synthesis by Escherichia coli and Salmonella enterica serovar Typhimurium

Abstract: Production of curli (AgF) adhesins by Escherichia coli and Salmonella enterica serovar Typhimurium (S. typhimurium) is associated with extracellular matrix production and is optimal at low temperature during stationary phase. Curli and extracellular matrix synthesis involves a complex regulatory network that is dependent on the CsgD (AgfD) regulator. We have identified a novel regulator, termed MlrA, that is required for curli production and extracellular matrix formation. Two cosmids from a genomic library of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
150
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(153 citation statements)
references
References 68 publications
2
150
0
1
Order By: Relevance
“…Approximately 10,000 transformants were screened, and three rdar-positive isolates were obtained. Plasmids purified from all three isolates contained mlrA (yehV), a known positive regulator of agfD transcription (13,22). When Sarc1 was transformed with pBR322 containing only mlrA, this was sufficient to restore the rdar morphotype (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Approximately 10,000 transformants were screened, and three rdar-positive isolates were obtained. Plasmids purified from all three isolates contained mlrA (yehV), a known positive regulator of agfD transcription (13,22). When Sarc1 was transformed with pBR322 containing only mlrA, this was sufficient to restore the rdar morphotype (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Mycobacterium bovis bacillus Calmette-Guérin (BCG) is one well-documented example of this phenomenon (6), which has also occurred in several commonly studied bacterial pathogens (21). The initial descriptions of curli (Tafi) (43) and the positive regulators crl (3) and mlrA (13) were for E. coli HB101, a commonly used strain with trans regulatory mutations. Garcia et al (22) have also recently described a variant of the commonly used S. enterica serovar Typhimurium SL1344 with a trans regulatory mutation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The binding of K-12 strains to plant and mammalian cells was promoted by the addition of the cah, aidA1, or csg gene to the bacteria, suggesting that all of their gene products can participate in binding to both types of surfaces. While E. coli K-12 strains possess the genes for curli biosynthesis and a cah homologue gene (agn-43), it has been shown that the expression of their protein products is repressed or the genes are inactivated (6,17,21,45), which renders them unable to interfere with the phenotypes observed.…”
Section: Discussionmentioning
confidence: 99%
“…agfD is also regulated by the transcriptional regulators OmpR, MlrA and CpxR-P (Gerstel and Rö mling, 2003;. s 38 not only directly regulates agfD, but also feeds into its activation via positive regulation of the transcriptional regulator mlrA, (Brown et al, 2001). Expression of agfD is initiated in late exponential phase with a peak in early stationary phase, which results in initiation of transcription of the rest of the fimbrial biosynthetic genes, and other genes in the regulon including adrA, (Rö mling et al, 2000) which is involved in regulating cellulose biosynthesis.…”
Section: Introductionmentioning
confidence: 99%